Reduced phosphodiesterase-2 activity in the amygdala results in anxiolytic-like effects on behavior in mice. (May 2019) - Chen, Ling; Cui, Suying; Yu, Haiyang; Li, Gaowen; Liu, Na; Wu, Qiang; Zhang, Han-Ting; O'Donnell, James M; Wang, Gang; Xu, Ying
Background: Phosphodiesterase-2 (PDE2) is a cyclic nucleotide phosphodiesterase and is highly expressed in the amygdala, which suggests its important role in anxiety-like behavior. Aims: The present study examined whether reduced PDE2A expression in the central nucleus of the amygdala (CeA) produces anxiolytic-like effects in mice. Methods: PDE2A knockdown in amygdaloid (AR5) cells or the CeA was established using a lentiviral vector-based siRNA system. The anxiety-like behaviors were detected by the elevated plus maze (EPM) and hole-board tests in mice. The related proteins involved in cAMP/cGMP-dependent signaling, such as specific marker VASP ser239, CREB ser133 and BDNF were detected by immunoblot analysis. Results: PDE2A inhibition in AR-5 cells resulted in increases in cAMP/cGMP-related pVASP ser239 and pCREB ser133 . Behavioral tests showed that PDE2A knockdown in the CeA induced anxiolytic-like effects as evidenced by the increases in percentages of open-arm entries and time spent in the open arms in the EPM test, and the increases in head dips and time spent in head dipping in the hole-board test. However, these anxiolytic-like effects were antagonized by pre-treatment of soluble guanylyl cyclase inhibitor ODQ or adenylate cyclase inhibitor SQ. Furthermore, PDE2A knockdown significantly increased pVASP Ser239, pCREB Ser133 and decreased BDNF expression in the amygdala. Pre-intra-CeA of ODQ or SQ reversed or partially prevented the eﬀects of PDE2A knockdown on these proteins. Conclusions: The results suggest that PDE2A plays a crucial role in the regulation of anxiety by the cGMP/cAMP-dependent pVASP-pCREB-BDNF signaling pathway.